Recovery of sympathetic skin response after central corpectomy in patients with moderate and severe cervical spondylotic myelopathy. (4th March 2017) - Revanappa, Kumbhar Kartik; Moorthy, Ranjith K.; Alexander, Mathew; Rajshekhar, Vedantam
Abstract: Background: There are sparse data on the recovery of sympathetic skin response (SSR) following decompressive surgery in patients with cervical spondylotic myelopathy (CSM). We designed a study to assess SSR in patients with moderate and severe (Nurick grades 3, 4 and 5) CSM, and its recovery following central corpectomy (CC). Method: We conducted a prospective study on 19 patients with moderate and severe CSM who underwent CC from June 2008 to December 2010. Autonomic dysfunction was defined as the presence of 'bladder dysfunction' or 'orthostatic hypotension'. All patients underwent SSR test preoperatively and at follow-up. Functional evaluation was done using Nurick grade and modified Japanese Orthopedic Association (mJOA) score preoperatively and at follow-up. Findings: In the preoperative assessment, 14 of 19 (73.7%) patients had bladder dysfunction and orthostatic hypotension. SSR was absent in 13 (68.4%) patients preoperatively. At a mean follow-up of 14.5 months after CC, SSR was present in 12 of the 14 patients available for follow-up. SSR returned postoperatively in 9 of the 11 patients in whom it was absent preoperatively. Recovery of SSR postoperatively had significant correlation with improvement in Nurick grade ( p  =0.02), improvement in lower limb component of mJOA score ( p  =0.001) and Nurick grade recovery rate ( p  = 0.008). Conclusions: Dysfunction of the autonomic pathways as determined by the SSR is seen in nearly 70% of patients with moderate and severe CSM but did not correlate with other autonomic functions, suggesting possibly different pathways for different autonomic functions. Following uninstrumented CC, SSR returned in almost 80% of patients in whom it was absent preoperatively and this correlated significantly with improvement in functional grade. Decompressive surgery can reverse autonomic dysfunction in most of these patients.